Evaluasi Pola Asuh Grand Parenting Pada Karakter Anak SD - Intan Maulidah; Elma Ayu Pratama; Rika Izzatun Nikmah; Muhammad Nofan Zulfahmi (Inspirasi Dunia: Jurnal Riset Pendidikan dan Bahasa, 2025)
This research aims to evaluate the grand parenting approach and its influence on the character development of elementary school children. Grand parenting, which involves grandparents in the caregiving process, plays a crucial role in shaping children's values and attitudes. The methodology employed in this study is a qualitative approach, utilizing in-depth interviews and observations to assess the interactions between grandparents and their grandchildren. The findings reveal that the parenting styles implemented by grandparents significantly contribute to the character development of children, which includes aspects such as moral values, discipline, responsibility, and social skills. Furthermore, the strong emotional bonds between grandparents and grandchildren provide a sense of security and support essential for character development. This indicates the vital role of older generations in supporting children's character education and the need for increased attention to intergenerational relationships within families. This study recommends enhancing the involvement of grandparents in the educational processes of children, as well as the necessity for programs that foster intergenerational collaboration.